Excitatory/inhibitory ratio disruption modulates neural synchrony and flow directions in a cortical microcircuit. - Nobuhiko Wagatsuma; Sou Nobukawa; Tomoki Kurikawa (PLoS Computational Biology)
Autism spectrum disorder (ASD) and schizophrenia are complex and heterogeneous mental disorders involving the dysfunction of multiple neural systems. The atypical and heterogenous temporal coordinations of neuronal activity, which are widely observed in these two disorders, are hypothesized to stem from an excitatory/inhibitory (E/I) imbalance in the brain. To investigate the association between the E/I imbalance and atypical neural activities, and to assess the influence of specific subtypes of inhibitory interneurons on network activity regulation, we developed a computational microcircuit model with biologically plausible layer 2/3 of visual cortex that combined excitatory pyramidal neurons with three subtypes of inhibitory interneurons (parvalbumin [PV], somatostatin [SOM], and vasoactive intestinal polypeptide [VIP]). We numerically explored the role of distinct types of E/I imbalance by changing the population size of different subtype neurons. We find that when the E/I balance is disrupted by decreasing the PV population size, activity of the PV population precedes that of the pyramidal population, which enhances beta and gamma oscillations. Conversely, pyramidal neuronal population activity was the precursor of PV interneuron activity when the E/I imbalance was induced by decreasing the SOM population size; this preferentially impaired gamma-frequency activity. The disruption of E/I balance altered the information flow between pyramidal and PV populations, modulating neuronal dynamics. Our results suggest that E/I imbalance due to different subtype interneurons would induce the distinct types of the atypical neural behaviors associated with neural system dysfunction.